UPAYA MENINGKATKAN PRESTASI BELAJAR MELALUI MEDIA AUDIO VISUAL GERAK KELAS V SEKOLAH DASAR SANTO. PETRUS MEDAN - Pasaribu, Maria Nur Setia; Sihotang, Din Oloan (STIPAS Keuskupan Agung Kupang, 2024)
Through two cycles of Classroom Action Research (CAR), this study assesses the use of audio-visual materials to enhance the learning achievement of fifth-grade students at St. Elementary School. Data were collected using pretests and posttests. In the first cycle, students had an average score of 59, classified as